MODELLING OF PRICE DEMAND ELASTICITY FOR ENTRY TO BUS TERMINAL (Perner's Contacts, 2009)
This article deals with modelling of price demand elasticity for entry to bus terminal. Model was applied to concrete bus terminal – ÚAN Praha Florenc.
Keywords: Price demand elasticity; price demand elasticity coefficient; linear regressive model; distant and influential observation; bus terminal